2015
DOI: 10.1016/j.jfoodeng.2015.07.037
|View full text |Cite
|
Sign up to set email alerts
|

Influence of surfactant and processing conditions in the stability of oil-in-water nanoemulsions

Abstract: a b s t r a c tThis work evaluates the influence of the type of surfactant (Tween 20, SDS and DTAB) and processing conditions on the stability of oil-in-water nanoemulsions, measured in terms of hydrodynamic diameter (H d ), polydispersity index (PdI) and zeta potential (Zp). Nanoemulsions were prepared using high-pressure homogenization based on a 2 4 level factorial design. Results show that processing parameters such as homogenization pressure, surfactant concentrations and oil:water ratio significantly aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
77
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(86 citation statements)
references
References 40 publications
8
77
0
1
Order By: Relevance
“…The choice of low molecular weight surfactants also contributed to the small‐sized droplets. This occurs due to the greater ease and speed of droplet adsorption during homogenization, and greater reduction of interfacial tension . Moreover, the combination of surfactants causes a greater decrease in the interfacial tension between water and oil, thus causing an efficient reduction in droplet size and in the tendency of the droplets for coalescence, consequently improving the stability of NEs when compared to NEs which use only one surfactant (Figures and ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The choice of low molecular weight surfactants also contributed to the small‐sized droplets. This occurs due to the greater ease and speed of droplet adsorption during homogenization, and greater reduction of interfacial tension . Moreover, the combination of surfactants causes a greater decrease in the interfacial tension between water and oil, thus causing an efficient reduction in droplet size and in the tendency of the droplets for coalescence, consequently improving the stability of NEs when compared to NEs which use only one surfactant (Figures and ).…”
Section: Discussionmentioning
confidence: 99%
“…High-energy emulsifier-high-pressure homogenization technique was chosen for the preparation of NE for its better scalability to an industrial production, ease of operation and good reproducibility when compared to low energy emulsification method. [16,29] In addition, previous studies have demonstrated that NEs produced by methods involving high emulsification energy tend to be more stable than those produced by low-energy emulsification methods. This is due to the fact that smaller droplets are formed and are capable of avoiding destabilization phenomena, such as Ostwald ripening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to McClements (2015), agitation with a high speed facilitates the oil solubilization during the emulsification process, which explains the smaller diameter obtained for the nanoemulsion developed at 10,000 rpm. Regarding the concentration of the surfactant, this variable affects the size of globules and consequently the emulsion stability (Silva et al, 2015;Bernardi et al, 2011). High surfactant concentrations cause an increased interfacial area while reducing the interfacial tension, resulting in smaller droplet size (Pengon et al, 2018).…”
Section: Average Diameter Of Emulsionsmentioning
confidence: 99%
“…The physicochemical properties and stability of nanoemulsions are influenced by the process conditions (McClements, 2011;Silva et al, 2015). On a stable system, the globules dispersed in nanoemulsions maintain their initial characteristics and remain uniformly distributed by a continuous phase (Chung & McClements, 2018).…”
Section: Introductionmentioning
confidence: 99%